2021
DOI: 10.2147/clep.s308220
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and All-Cause, Cardiovascular Disease, Cancer Mortality Among Adults with and without Diabetes

Abstract: Aim: To examine the association of psychological distress with all-cause, cardiovascular disease (CVD) and cancer mortality in US adults, and verified whether the associations differed between participants with and without diabetes. Methods: A total of 485,864 adults (446,288 without diabetes and 39,576 with diabetes) who participated in the National Health Interview Survey from 1997 to 2013 were linked to the National Death Index through December 31, 2015. Psychological distress was measured by the Kessler 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
2
6
0
1
Order By: Relevance
“…In IPD-Work, work-related stress was not associated with total mortality among healthy employees, but a 1.6-fold increased risk of death was observed among stressed men with cardiometabolic disease (diabetes, myocardial infarction or stroke), with the contribution of stress being clinically significant and independent of conventional risk factors and their treatment 156 . A similar interaction was observed in another large-scale study of over 485,000 adults who participated in the National Health Interview Survey 157 . During 8-year follow-up, severe psychological distress was associated with a 2-fold increased risk of death in individuals with diabetes but only 1.5-fold increased risk in non-diabetic people, while the corresponding relative risks were 2.0-and 1.4fold for cardiovascular deaths.…”
Section: Stress and Disease Progressionsupporting
confidence: 80%
“…In IPD-Work, work-related stress was not associated with total mortality among healthy employees, but a 1.6-fold increased risk of death was observed among stressed men with cardiometabolic disease (diabetes, myocardial infarction or stroke), with the contribution of stress being clinically significant and independent of conventional risk factors and their treatment 156 . A similar interaction was observed in another large-scale study of over 485,000 adults who participated in the National Health Interview Survey 157 . During 8-year follow-up, severe psychological distress was associated with a 2-fold increased risk of death in individuals with diabetes but only 1.5-fold increased risk in non-diabetic people, while the corresponding relative risks were 2.0-and 1.4fold for cardiovascular deaths.…”
Section: Stress and Disease Progressionsupporting
confidence: 80%
“…Similar to the results previously published by Zaorsky et al [ 17 ], we found that the risk of CVM in BC patients was highest in the first 10 months after diagnosis. Meanwhile, the study by Fang and Ye et al suggested that newly diagnosed cancer may lead to psychological and emotional distress in cancer patients, which in part promotes the development of CVM [ 18 , 19 ]. Therefore, psychiatric assessment and psychological support are necessary for newly diagnosed BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…To create a comorbidities score, we used data the participants’ self-reported medical diagnosis of asthma, diabetes, hypertension, liver conditions, and/or weak or failing kidney function. In addition, we considered self-rated health (rated as excellent, very good, good, fair, or poor), mobility difficulties (not at all difficult/only a little; somewhat difficult to walk one-quarter of a mile [approximately 3 city blocks]; somewhat difficult to ascend 10 steps without resting), and psychological distress based on the Kessler 6 scale …”
Section: Methodsmentioning
confidence: 99%
“…In addition, we considered self-rated health (rated as excellent, very good, good, fair, or poor), mobility difficulties (not at all difficult/only a little; somewhat difficult to walk onequarter of a mile [approximately 3 city blocks]; somewhat difficult to ascend 10 steps without resting), and psychological distress based on the Kessler 6 scale. 16,17…”
Section: Covariatesmentioning
confidence: 99%